MATHEMATICAL MODELING OF MICROELECTRONIC TRANSMITTERS USING PETRI NET - Zafar Fakhridinovich Mirzarakhmedov (Journals Park Publishing, 2022)
Currently, microprocessor, microelectronic systems and devices used in railway automation and remote control systems are widely used. The use of systems and devices for railway automation and remote control, developed on the basis of microelectronics and microprocessor elements, provides an increase in the level of reliability compared to systems based on electromagnetic relays.In this article, the modeling of transmitter relays designed to transmit the codes generated by the KPTSH transmitter to road traffic lights and locomotive traffic lights in rail chains equipped with auto-blocking systems and automatic locomotive signaling systems at the joint-stock company «Uzbekistan Temir Yollari» is considered.
Keywords: automatic blocking, locomotive automatic signaling, track circuits, code, processes